The effect of biochar on growth performance and yield of rice: a review / Muhammad Faiz Hassan - Hassan, Muhammad Faiz (Faculty of Plantation and Agrotechnology, 2016)
Nowadays, fanners know about the benefits of applying biochar on the field. Thus, it makes them shift from inorganic to organic ways which is apparently gives many benefits to the cultivated crops and the soil itself. Biochar are widely produced from agricultural waste such as empty fruit bunch, rubber factory effluent, rice husk and other waste materials. Basically, the application of biochar would help to remove of toxic explosives from the soil and ground water supplies. Biochar can be used as the soil enhancer that gives numerous benefits for agricultural purposes. This paper highlighted the characteristics of biochar from plant residues resources and their effect to soil properties, growth performance and also yield of rice.